High-resolution ribosome profiling defines discrete ribosome elongation states and translational regulation during cellular stress - Wu, Colin Chih-Chien (Mol Cell, 2019)
Ribosomes undergo substantial conformational changes during translation elongation to accommodate incoming aminoacyl-tRNAs and translocate along the mRNA template. We used multiple elongation inhibitors and chemical probing to define ribosome conformational states corresponding to different sized ribosome-protected mRNA fragments (RPFs) generated by ribosome profiling. We show using various genetic and environmental perturbations that short 20–22 or classical 27–29 nucleotide RPFs correspond to ribosomes with open or occupied ribosomal A sites, respectively. These distinct states of translation elongation are readily discerned by ribosome profiling in all eukaryotes tested including fungi, worms and mammals. This high-resolution ribosome profiling approach reveals mechanisms of translation elongation arrest during distinct stress conditions. Hyperosmotic stress inhibits translocation through Rck2-dependent eEF2 phosphorylation whereas oxidative stress traps ribosomes in a pre-translocation state, independent of Rck2-driven eEF2 phosphorylation. These results provide insights and approaches for defining the molecular events that impact translation elongation throughout biology.